FOR GOLD AND THE BLESSING OF GOD: THE RATIONAL CHOICE FOR USING THE RABU WEKASAN AMULET IN THE EAST JAVANESE MUSLIM COMMUNITY - Devi Suci Windariyah; Maskud (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2023)
Several scholars have different opinions regarding the law of the Rabu Wekasan amulet that lives in the Javanese Muslim community. However, despite these differences, the East Javanese Muslim community still carries out and uses amulets to carry out these rituals. This research aims to determine amulet users' perspectives on life, mindset, and worldviews, especially in the Sempen, Sumbertengah, Mumbulsari, and Jember communities. Researchers use a rational choice theory where a person's actions are primarily determined by values or choices using data collection techniques such as interviews, observation, and documentation. The research results reveal three typologies of amulet users' mindsets: 1) Tabarrukan, using the Rabu Wekasan Amulet as a wasilah (intermediary) to ask for protection from Allah; 2) Economic aspect, using Rabu Wekasan amulets to protect their economic level from losses; and 3) Social aspect: using Rabu Wekasan amulets to maintain peace and public health.